A qualitative case study of telehealth for in-home monitoring to support the management of type 2 diabetes. (October 2013) - Carlisle, Karen; Warren, Robin
The present study formed part of a randomised controlled trial of telehealth for in-home monitoring to support people with poorly controlled type 2 diabetes. We explored the experiences of patients and healthcare practitioners, and their perceptions of the telehealth model of care used in the trial. In addition to their usual diabetes care, participants receive diabetes care from a diabetes educator nurse via an in-home broadband communication device. On average, each patient participated in 14 videoconferences with a diabetes care coordinator during the 12-month trial period. Qualitative data was collected from two general practices and included semi-structured interviews and document review of patient clinical notes. A total of 12 people were interviewed: 8 health practitioners and 4 patients. Patients and health practitioners expressed a high level of satisfaction with the model of care provided. Patients also reported positive health and social outcomes as a result of being involved in the trial and indicated that in the main they had achieved their goals and were happy with their progress over the 12-month period. Analysis of interviews revealed three broad elements associated with the implementation of telehealth: interpersonal factors, operational problems and the wider health system context within which the general practices and trial team were operating. The findings suggest that adopting telehealth in the management of type 2 diabetes can lead to improved diabetes control, but more support is required to ensure sustainability and widespread implementation.